2021
DOI: 10.1097/aco.0000000000001063
|View full text |Cite
|
Sign up to set email alerts
|

Management of postoperative nausea and vomiting in adults: current controversies

Abstract: Purpose of reviewPostoperative nausea and vomiting (PONV) continue to plague the surgical patient population with an adverse impact on postoperative outcomes. The aim of this review is to critically assess current evidence for PONV management, including studies evaluating baseline risk reduction and antiemetic prophylaxis, to provide a pragmatic approach to prevention and treatment of PONV in routine clinical practice. Recent findingsMultiple recent reviews and guidelines have been published on this topic with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
(60 reference statements)
0
22
0
Order By: Relevance
“…Although multiple comprehensive guidelines and risk assessment models have been published on the subject, PONV continues to plague the surgical population. The most likely reason is the lack of compliance with nausea and vomiting prevention guidelines 19 . Pysyk et al reported that the incidence of PONV was reduced by annual anesthesiologist performance feedback urging the use of antiemetic medications 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple comprehensive guidelines and risk assessment models have been published on the subject, PONV continues to plague the surgical population. The most likely reason is the lack of compliance with nausea and vomiting prevention guidelines 19 . Pysyk et al reported that the incidence of PONV was reduced by annual anesthesiologist performance feedback urging the use of antiemetic medications 20 .…”
Section: Discussionmentioning
confidence: 99%
“…All patients irrespective of their PONV risk status should receive antiemetic prophylaxis with a combination of 2 to 3 antiemetics from different classes. 32 A commonly used combination includes dexamethasone (8 to 10 mg) given intravenously after induction of anesthesia. It is preferred due to its long duration of action, analgesic efficacy, as well as potentiation of peripheral nerve blocks.…”
Section: Postoperative Nausea and Vomiting (Ponv) Prophylaxismentioning
confidence: 99%
“…It is preferred due to its long duration of action, analgesic efficacy, as well as potentiation of peripheral nerve blocks. 32 Also, a single dose of dexamethasone 8 to 10 mg is safe and does not increase adverse events such as wound infection and healing. In addition, 5-hydroxytryptamine [HT]-3 receptor antagonists such as ondansetron (4 mg, IV) should be given at the end of the surgical procedure.…”
Section: Postoperative Nausea and Vomiting (Ponv) Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative nausea and vomiting (PONV) is one of the most common adverse effects of general anesthesia, with an incidence of 30–80% [ 9 ]. In the context of major abdominal surgery, careful attention should be paid to adequate PONV prophylaxis [ 10 ]. A multimodal approach within an enhanced recovery after surgery pathway allows the majority of patients to resume feeding on postoperative day 1 [ 11 ].…”
Section: Potential Advantages Of Tiva For Hepatic Resectionmentioning
confidence: 99%